Treaty Series 2161 - United Nations (United Nations, 2004)
In accordance with Article 102 of the Charter and the relevant General Assembly Resolutions, every treaty and international agreement registered or filed and recorded with the Secretariat since 1946 is published in the United Nations Treaty Series. At present, the collection includes about 30,000 treaties reproduced in their authentic languages, together with translations into English and French, as necessary. The Treaty Series, where treaties are published in the chronological order of registration, also provides details about their subsequent history (i.e., participation in a treaty, reservations, amendments, termination, etc.). Comprehensive Indices covering 50-volume-lots are published separately. A Standing Order service is available for the Series and out-of-print volumes are available on microfiche.